The feeding of dietary Codonopsis pilosula polysaccharide enhances the immune responses, the expression of immune-related genes and the growth performance of red swamp crayfish (Procambarus clarkii). Issue 103 (August 2020) - Liu, Fei; Geng, Chao; Qu, Yun-Kun; Cheng, Bo-Xing; Zhang, Yao; Wang, Ai-Ming; Zhang, Jia-Hong; Liu, Bo; Tian, Hong-Yan; Yang, Wen-Ping; Yu, Ye-Bing; Chen, Zhong-Bing
Abstract: Polysaccharides have many functions in aquatic animals and are widely used as immunopotentiators. However, despite the emergence of serious diseases, few studies have explored the effects of Codonopsis pilosula polysaccharide (CPP) on crustaceans. We studied the effects of CPP on the growth performance, nonspecific immunity, antioxidant activity and disease resistance of red swamp crayfish ( Procambarus clarkii ). Healthy crayfish (5.80 ± 0.1 g) were fed diets supplemented with 0% (control), 0.05%, 0.1%, 0.15%, 0.20%, and 0.30% CPP for 8 weeks. At the end of the 8-week feeding trial, the optimal final body weight (FBW), weight gain (WG), specific growth rate (SGR), and feed conversion ratio (FCR) were observed in the crayfish fed the diets with 0.15% and 0.20% CPP, followed by those fed the diet with 0.30% CPP and then those fed the diet with 0.10% CPP, whereas the values of these parameters were obtained with the control crayfish ( P < 0.05 ). The crayfish fed the diets with 0.15% and 0.20% CPP exhibited a significantly higher total hemocyte count (THC) and significantly increased phenoloxidase (PO), lysozyme (LZM), hemocyte (Hc), acid phosphatase (ACP) and alkaline phosphatase (AKP) compared with those belonging to the other groups ( P < 0.05 ). The crayfish fed the diets with 0.15% and 0.2% CPP exhibited significantly higher total superoxide dismutase (T-SOD) and glutathione peroxidase (GPx) activities, a significantly increased total antioxidant capacity (T-AOC) and a significantly lower malondialdehyde (MDA) content compared with the other groups ( P < 0.05 ), which indicated that antioxidant capacity was significantly induced by the CPP-supplemented diets. Significantly upregulated expression of immune-related genes (anti-lipopolysaccharide factors ( alf ), peroxiredoxin ( prx5 ), cathepsin B ( ctsb ), mitochondrial manganese superoxide dismutase ( mtMnsod ), cyclophilin A ( cypa ), glutathione peroxidase ( gpx ), Toll-like receptor 3 ( tlr 3), and heat shock protein 70 ( hsp 70)) was detected in the crayfish fed the diets supplemented with 0.15% and 0.20% CPP diet compared with the levels observed in the control crayfish. These results showed that dietary CPP supplementation greatly improved the growth, immunity and antioxidant capacities of crayfish, and according to the observed results, 0.15%–0.2% is the recommended optimal level of CPP dietary supplementation for crayfish. Highlights: CPP increases the WG and SGR and decreases the FCR of crayfish. CPP affects the expression of immune-related genes in crayfish. CPP synergistically increases crayfish immune function. CPP increases the survival rate of crayfish after WSSV infection.